Analysis of Financial Ratio to Economic Value Added at PT. Sharia People's Financing Bank (BPRS) Puduarta Insani Deli Serdang - Nina Andriany Nasution; Fitri Yani Panggabean; Khairani Agustin (Universitas 17 Agustus 1945 Semarang, 2024)
This research aims to analyze the Financial Ratio to Economic Value Added at PT. Sharia People's Financing Bank (BPRS) Puduarta Insani Deli Serdang. Specifically, to analyze the measurement of Return On Equity (ROE) and Debt to Equity Ratio (DER) on Economic Value Added (EVA). The research approach uses Quantitative with Regression Data Type from 2016 - 2023, Multiple Linear Regression analysis techniques. The results of this research are: 1) Return On Equity (ROE) has a positive and partially significant effect on Economic Value Added (EVA), because an increase in equity can increase the added value of positive Economic Value Added (EVA) at PT. Sharia People's Financing Bank (BPRS) Puduarta Insani Deli Serdang; 2) Debt to Equity Ratio (DER) has a negative and partially significant effect on Economic Value Added (EVA), because debt that exceeds the asset value can reduce the equity value. Low Equity will cause a negative Economic Value Added (EVA) value at PT. Sharia People's Financing Bank (BPRS) Puduarta Insani Deli Serdang; 3) Return On Equity (ROE) and Debt to Equity Ratio (DER) simultaneously have a positive and significant effect on Economic Value Added (EVA) at PT. Sharia People's Financing Bank (BPRS) Puduarta Insani Deli Serdang.